Hypomagnesemia in Brachycephalic Dogs - Mellema, M.S. (J Vet Intern Med, 2014)
BACKGROUND: Brachycephalic dogs are at risk for arterial hypertension and obstructive sleep apnea, which are both associated with chronic magnesium (Mg) depletion. HYPOTHESIS/OBJECTIVES: To compare the period prevalence of hypomagnesemia between Boxers and Bulldogs presented to a referral teaching hospital. To screen a group of Bulldogs for evidence of hypomagnesemia, and to obtain pilot data regarding the utility of parenteral Mg tolerance testing (PMgTT) in the diagnosis of whole‐body Mg deficiency. ANIMALS: Chemistry laboratory submissions were retrospectively analyzed for serum total Mg (tMg) in Boxers and Bulldogs. Prospectively, 16 healthy client‐owned Bulldogs were enrolled. METHODS: Retrospective case study. tMg concentrations were compared between Boxers and Bulldogs. Dogs with low serum albumin or high serum creatinine concentrations were excluded. Prospectively, ionized Mg (iMg), tMg, and arterial blood pressure were measured and iMg‐to‐tMg ratio (iMg : tMg) was calculated. Parenteral Mg tolerance testing (PMgTT) was performed in 3/16 dogs. RESULTS: In the retrospective study, period prevalence of hypomagnesemia was 4.7% in Boxers and 15% in Bulldogs (P = .02). The risk ratio for hypomagnesemia in Bulldogs was 1.8 when compared to Boxers (CI: 1.3–2.7). In the prospective study, iMg was [median (interquartile)] 0.43 (0.42–0.46) mmol/L (reference range 0.4–0.52), tMg was 1.9 (1.8–1.9) mg/dL (reference range 1.9–2.5). iMg : tMg was [mean (±SD)] 0.59 ± 0.04. Percentage retention after PMgTT were 55%, 95%, and 67%, respectively. CONCLUSIONS AND CLINICAL IMPORTANCE: Mg deficiency is common in Bulldogs and could contribute to comorbidities often observed in this breed. iMg : tMg and PMgTT might prove helpful in detecting chronic subclinical Mg deficiency.